Analisis Kapasitas Saluran Parit 2 Desa Riak Siabun 1 Kabupaten Seluma Provinsi Bengkulu (Inersia: Jurnal Teknik Sipil, 2025)
This research aim to knowing about the problems of flooding and standing water on Parit 2 channel in Riak Siabun 1, Seluma regency that occur continuously every rainy season. This indicates that water volume which come into channel exceed the normal capacity of channel. Calculation of discharge with the rational methods use 3 primary factors, they are maximum rainfall intensity, wide of area and run off coefficient. The method of analysis used in this study include hydrologic analysis using Gumbel Distribution method which calculates the discharge capacity of the channel and hydraulic analysis to channel normalization. The result of the calculation shows that the channel capacity (Qs) in Parit 2 is 1.95 m3/sec with the upper width 0f 3,9 m; width of 2,74 m and wet cross section 0,744 m smaller than compared to flood peak discharge (QP) of 2,525 m3/sec. It is necessary to normalize the channel by reviewing the channel with a upper width of 4,5 m; width of 3 m and wet coress section 1 m so as to obtain channel discharge of 4,63 m3/sec, then the planning channel can be received. Keywords: flood, debit, intensity, channel normalization